2015
DOI: 10.1371/journal.ppat.1004789
|View full text |Cite|
|
Sign up to set email alerts
|

Selection and Spread of Artemisinin-Resistant Alleles in Thailand Prior to the Global Artemisinin Resistance Containment Campaign

Abstract: The recent emergence of artemisinin resistance in the Greater Mekong Subregion poses a major threat to the global effort to control malaria. Tracking the spread and evolution of artemisinin-resistant parasites is critical in aiding efforts to contain the spread of resistance. A total of 417 patient samples from the year 2007, collected during malaria surveillance studies across ten provinces in Thailand, were genotyped for the candidate Plasmodium falciparum molecular marker of artemisinin resistance K13. Para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
106
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(128 citation statements)
references
References 30 publications
16
106
1
Order By: Relevance
“…pears to be increasing in this region of Kenya, and (iii) gene mutations associated with CQ resistance (Pfcrt CVIET and Pfmdr-1 N86Y) are on the decline. A total of at least 12 polymorphisms in the K13 propeller domain were recently implicated in artemisinin resistance in Southeast Asia (19)(20)(21)37). Similar to previous studies conducted in Africa (38-40), we did not observe any mutations in the propeller domain of the K13 gene that we sequenced.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…pears to be increasing in this region of Kenya, and (iii) gene mutations associated with CQ resistance (Pfcrt CVIET and Pfmdr-1 N86Y) are on the decline. A total of at least 12 polymorphisms in the K13 propeller domain were recently implicated in artemisinin resistance in Southeast Asia (19)(20)(21)37). Similar to previous studies conducted in Africa (38-40), we did not observe any mutations in the propeller domain of the K13 gene that we sequenced.…”
Section: Discussionsupporting
confidence: 87%
“…The reaction mixtures were precipitated in 70% ethanol to clean up dye terminators, rehydrated in 10 l HiDi formamide, and then sequenced on a 3130xl ABI genetic analyzer (ABI Prism, CA, USA). In addition, the K13 propeller domain associated with artemisinin resistance was sequenced as recently described (37). Sequence analysis was performed by using Geneious R7 (Biomatters, Auckland, New Zealand).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, another artemisinin resistance gene called kelch k13-propeller domain containing gene was reported (21). The k13-propeller domain was amplified using a nested PCR method previously described (21,22). The sequence data was analyzed using Geneious Pro R8 to identify polymorphisms associated with artemisinin resistance.…”
Section: Drug Resistance Marker Surveillancementioning
confidence: 99%
“…It is possible that mutations within these genes might be necessary for the survival of parasites carrying artemisinin resistance-associated mutations in the Pfkelch13 gene in the absence of artemisinin selection pressure. This could explain the observation that artemisinin-resistant P. falciparum has emerged multiple times in Southeast Asia, where polymorphisms of these loci were prevalent, but not in Africa, where nearly all of these loci are of the wild type (36)(37)(38). Laboratory studies have shown, however, that African parasites can display reduced sensitivity to artemisinin when specific mutations are artificially induced in Pfkelch13 (7).…”
Section: Hap_1 T G G T a G T T T G T A C C A G G C G G A T Gmentioning
confidence: 99%